Legal Protection Against Cyber Crime Threats for Business Economics 4.0 - Didi Sukardi (IHSA Institute, 2022)
Appearance crime cyber (cybercrime) is motivated by progress technology that doesn't balanced by progress resource man as well as omissions made by tempted users _ _ with lure gifts given by parties who do not responsible on behalf of the other party as amplifier that that true and not fraud , as well most from users _ tempted will lure present the so that give room for people to To do crime cyber . Study this character descriptive in form protection law for perpetrator economy business 4.0 against threat cyber crime according to Law No. 11 of 2008 on ITE. As for results study this is that principle protection law for perpetrator economy business 4.0 that is with existence provision from Article 1320 of the Civil Code which contains : condition happening agreements , threats and challenges as well as the obstacles faced by the perpetrators economy business 4.0 which is all is serious threat , and form protection law for the perpetrators effort that is provision law that can used to drag the perpetrators of the cyber crime new limited to regulations statute book of law Law Criminal Code (KUHP) and Law no. 11 of 2008 concerning ITE.